Let a , b , c be non-zero real constants such that ∫ 0 3 ( 3 a x 2 + 2 b x + c ) d x = ∫ 1 3 ( 3 a x 2 + 2 b x + c ) d x . What is the value of a + b + c ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Or you can directly say ∫ 0 1 ( 3 a x 2 + 2 b x + c ) d x = 0 :)
Thinking about it logically, as in with the basic area formula length times width, we have two areas equalling each other that have different lengths. It's like saying 3x = 2x. The only solution for the width is zero. Therefore, a, b, and c have to be zero.
Then of course, 0 + 0 + 0 = 0
Please observe, that a, b and c should be non-zero real constants, as described in the task. I had the same thought at the beginning.
It explicitly states that a, b, c are non-zero.
Let f ( x ) = 3 a x 2 + 2 b x + c
∫ 0 3 f ( x ) d x = ∫ 0 1 f ( x ) d x + ∫ 1 3 f ( x ) d x = ∫ 1 3 f ( x ) d x so that 0 = ∫ 0 1 f ( x ) d x = a x 3 + b x 2 + c x ∣ ∣ ∣ 0 1 = a + b + c
Problem Loading...
Note Loading...
Set Loading...
Let, f ( x ) = ∫ ( 3 a x 2 + 2 b x + c ) d x = a x 3 + b x 2 + c x [We won’t need the integral constant as it’s a definite integral.]
Given that, ∫ 0 3 ( 3 a x 2 + 2 b x + c ) d x = ∫ 1 3 ( 3 a x 2 + 2 b x + c ) d x ⇒ [ a x 3 + b x 2 + c x ] 0 3 = [ a x 3 + b x 2 + c x ] 1 3 ⇒ f ( 3 ) − f ( 0 ) = f ( 3 ) − f ( 1 ) ⇒ f ( 1 ) = f ( 0 ) ⇒ a + b + c = 0